Continuity of care in suicide prevention: current status and future directions - Arnon, Shay; Shahar, Golan; Brunstein Klomek, Anat (Frontiers in Public Health, 2024)
Introduction: Continuity of Care (CoC) is central to suicide prevention. The present study aims to review contemporary definitions, operationalization in research, and key components of CoC in the prevention of suicide. Methods: The present study is a narrative review. A thorough search of available literature on CoC and suicidality was conducted. Studies published between 1995-2021 were reviewed and selected based on relevance to CoC and suicidality. Selected research was subsequently summarized to outline definitions of CoC, its operationalization in research, and key components for suicide prevention. Results: the definition, measurement, and operationalization of CoC in suicide prevention varies tremendously, derailing clinical practice. Key elements of CoC identified across the literature include (1) CoC across multiple levels of care, (2) the role of primary care providers and case managers in CoC of suicidal patients (3) the importance of follow up contact with suicidal patients post-treatment, and (4) the role of national and institutional guidelines for CoC of suicidal patients. Limitations: There is a dearth of randomized controlled trials and insufficient evidence on specific populations. Conclusions: CoC refers to a wide, complex concept that must be broken down into specific categories that can provide more nuanced guidance of research and clinical implications.